Peer Conformity and Its Link to Bullying Among Upper Elementary Students: Konformitas Teman Sebaya dan Kaitannya dengan Perundungan di Kalangan Siswa Sekolah Dasar Kelas Atas - Rachmawati, Henny; Laili, Nurfi (Psikologia : Jurnal Psikologi, 2025)
Bullying refers to acts of violence perpetrated by individuals or groups that are seen as "stronger." This research aims to examine the connection between peer conformity and bullying behavior among students in grades 4 to 6 at MI Nailul Ulum Bangun. The methodology used is a quantitative correlational approach, which seeks to identify whether a relationship exists between two or more variables. A saturated sampling method was employed, encompassing a total population of 105 students. The data were analyzed utilizing the Pearson Product Moment correlation technique. Results from hypothesis testing indicated a significant relationship between variable X (peer conformity) and variable Y (bullying behavior), with a two-tailed significance value of 0.00, which is less than 0.05, and a positive correlation coefficient of 0.553. Highlights: Significant Correlation – The study found a strong positive correlation (r = 0.553) between peer conformity and bullying behavior among students. Quantitative Approach – Using a correlational method and Pearson Product Moment analysis, the research statistically confirmed the relationship between the variables. Saturated Sampling – The study included all 105 students from grades 4 to 6 at MI Nailul Ulum Bangun, ensuring comprehensive data representation. Keywords: Peer Conformity, Bullying Behavior, Elementary School Students